2022
DOI: 10.1029/2021gl097076
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Waves Controlling the Effect of Energetic Electron Precipitation on the Northern Polar Vortex

Abstract: Energetic electron precipitation (EEP) forms ozone‐depleting nitrogen and hydrogen oxides in the high‐latitude middle and upper atmosphere, leading to ozone destruction and temperature enhancement that can strengthen the winter polar vortex. This EEP effect on polar vortex depends on quasi‐biennial oscillation and sudden stratospheric warmings, which earlier studies relate to planetary waves. We study here the possible modulation of the EEP effect by planetary waves. We perform a principal component analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 43 publications
5
11
0
Order By: Relevance
“…Here, less SSWs where observed during high A p winters when the QBO at the 30 hPa level in August, September and October was in the easterly phase. As SSWs are driven by planetary wave activity, Salminen et al (2022) have further investigated the EPP influence for different latitudinal planetary wave propagation patterns. The study found that EPP induced wave-mean-flow interactions have a stronger influence when more planetary waves propagate at mid latitudes (50°-52.5°) than at polar latitudes (70°-72.5°).…”
mentioning
confidence: 99%
“…Here, less SSWs where observed during high A p winters when the QBO at the 30 hPa level in August, September and October was in the easterly phase. As SSWs are driven by planetary wave activity, Salminen et al (2022) have further investigated the EPP influence for different latitudinal planetary wave propagation patterns. The study found that EPP induced wave-mean-flow interactions have a stronger influence when more planetary waves propagate at mid latitudes (50°-52.5°) than at polar latitudes (70°-72.5°).…”
mentioning
confidence: 99%
“…In mid‐winter, this results in cooler mesosphere and upper stratosphere due to increased infrared radiative cooling (Sinnhuber et al., 2018) and by the following dynamical impact to warmer lower stratosphere (Salminen et al., 2019) and weaker than average polar vortex with more frequent SSWs compared to the average occurrence rate under the easterly QBO. The EEP influence on the polar vortex is known to preferentially occur, when the planetary wave activity to the vortex is suitably enhanced, for example, during easterly QBO phase (Asikainen et al., 2020; Salminen et al., 2022). On the other hand, the geomagnetic activity influence on SSW probability can also be interpreted so that in QBO‐E larger than average geomagnetic activity (EEP) strengthens the polar vortex and makes it less prone to SSWs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased adiabatic heating related to the BDC associated downwelling at high latitudes in QBO‐E also contributes to weakening of the vortex. Recent studies have shown that the weaker vortex associated with planetary wave forcing favors wave‐mean‐flow interactions by which the energetic electron precipitation can affect the polar vortex dynamics (Asikainen et al., 2020; Salminen et al., 2019, 2022). The exact reason why the QBO time lag from August to the winter season seems to be relevant for the EEP effect on the vortex warrants a more detailed study.…”
Section: Geomagnetic Activity Effect On Ssw Occurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previous research results, there is indeed a signal of GA in the atmospheric circulation in the NH, and planetary wave-mean flow interactions may be key to linking GA and dynamic response in the stratosphere (Lu et al, 2008;Salminen et al, 2022). Planetary waves are disturbances mostly originating from the Earth's surface, propagating in the westerly flow and inputting the easterly momentum, thereby, dissipating and decelerating the background flow.…”
mentioning
confidence: 94%